Imagining Okinawa: Japanese pop musicians and Okinawan music - Gillan, Matt (Perfect Beat, 2009)
Since the early 1970s, Okinawan styles have become popular throughout Japan and, to some extent, the rest of the world. This music has been performed both by native Okinawan musicians, and also by musicians from the Japanese mainland, drawn partly by the exoticness of this ‘Japanese other’. While modern-day Okinawan music has been considered from the perspective of Okinawan identity within a Japanese framework, the role of Japanese musicians in the recent Okinawan music boom has been overlooked. In this paper I present an overview of the activities of Japanese mainland musicians in their use of Okinawan musical material and, through an analysis of published interviews and writings by these musicians, I examine the cultural meanings that these musical expropriations have held. In addition, I argue that the activities of Okinawan musicians themselves have been greatly affected by mainland Japanese musicians, and that modern Okinawan music must be seen within a national musical context.